Исключение влияния переменных режимов работы турбоагрегатов на процесс диагностирования комплексным методом - Божко, А. Е.; Белых, В. И.; Зализняк, О. А. (НТУ "ХПИ", 2005)
The necessity of the complex analysis of fluctuations of basic and persistent bearings and control of the moments of change of speed the circulation of a rotor turbo-machines is shown at vibrating diagnostics. The monitoring system of change of speed the circulation of a rotor for application it is indicated at temporary selection of a vibrating signal
Keywords: работа турбины; скорость вращения ротора; угол наклона оси; дефекты лопаток; вибрация; подшипник